DETERMINATION OF GENETIC RELATIONSHIP IN TURKISH CHICKPEA (CICER ARIETINUM L.) GENOTYPES USING SSR MOLECULAR MARKERS AND CAPILLARY ELECTROPHORESIS - E. Atalay; M. Babaoğlu (Journal of Animal and Plant Sciences, 2012)
This study aimed to determinate the genetic relationship among 29 chickpea (Cicer arietinum L.) genotypes in Turkey using SSR markers. A total of 13 SSR primers were used for PCR amplifications, but the study was conducted with the data obtained from 10 SSR primers that yielded good results. PCR products were separated by the Beckman Coulter CEQ-8000 genetic analysis system with capillary electrophoresis and peak values of each primer were scored as presence (1) or absence (0) for all genotype. The dendrogram was constructed based on the genetic similarity coefficient using the UPGMA (unweighted pair group with arithmetic average) method with the computer software NTSYS-pc. Also, polymorphism rates, heterozygosity and polymorphic informaiton content were calculated using statistical formula. A total of 134 alleles were obtained from 10 primers and 122 of them were turned out to be polymorphic and the allele numbers obtained with SSR primers varied between 4 and 28. Heterozygosity also ranged between 0.23 and 0.42. Polymorphic information contents (PIC) varied between 0.70 and 0.89. Genetic similarity coefficients changed between 0.45 and 0.87. Chickpea genotypes identified among the very high level of similarity to that obtained from the dendogram branches intertwined. As a result, Turkish chickpea genotypes can be expressed in a very narrow genetic base.
Keywords: Chickpea; Cicer arietinum L.; SSR; capillary electrophoresis; genetic relationship.